Provider attitudes about childhood tuberculosis prevention in Lesotho: a qualitative study - Yael Hirsch-Moverman; Joanne E. Mantell; Limakatso Lebelo; Andrea A. Howard; Anneke C. Hesseling; Sharon Nachman; Koen Frederix; Llang Bridget Maama; Wafaa M. El-Sadr (BMC, 2020)
Abstract Background The World Health Organization estimated that 1.12 million children developed tuberculosis (TB) in 2018, and at least 200,000 children died from TB. Implementation of effective child contact management is an important strategy to prevent childhood TB but these practices often are not prioritized or implemented, particularly in low- and middle-income countries. This study aimed to explore attitudes of healthcare providers toward TB prevention and perceived facilitators and challenges to child contact management in Lesotho, a high TB burden country. Qualitative data were collected via group and individual in-depth interviews with 12 healthcare providers at five health facilities in one district and analyzed using a thematic framework. Results Healthcare providers in our study were interested and committed to improve child TB contact management and identified facilitators and challenges to a successful childhood TB prevention program. Facilitators included: provider understanding of the importance of TB prevention and enhanced provider training on child TB contact management, with a particular focus on ruling out TB in children and addressing side effects. Challenges identified by providers were at multiple levels -- structural, clinic, and individual and included: [1] access to care, [2] supply-chain issues, [3] identification and screening of child contacts, and [4] adherence to isoniazid preventive therapy. Conclusions Given the significant burden of TB morbidity and mortality in young children and the recent requirement by the WHO to report IPT initiation in child contacts, prioritization of child TB contact management is imperative and should include enhanced provider training on childhood TB and mentorship as well as strategies to eliminate challenges. Strategies that enable more efficient child TB contact management delivery include creating standardized tools that facilitate the implementation, tracking, and monitoring of child TB contact management coupled with guidance and mentorship from the district health management team. To tackle access to care challenges, we propose delivering intensive community health education, conducting community screening more efficiently using standardized tools, and facilitating access to services in the community.